Fabrics and pattern cutting - Aldrich, Winifred; Aldrich, James (Chichester, West Sussex, United Kingdom John Wiley & Sons, 2013)
"Getting the right cut for the right fabric is the key to good design. One of the most challenging aspects of a fashion designer's training is learning how to create patterns that utilise the characteristics of fabrics. With an ever expanding range available, an understanding of the relationship between fabric, form and pattern shape is now the most important skill a designer has to acquire. Winifred Aldrich, a leading pattern cutting authority, explores how a garment's shape is created and discusses the factors that need to be considered when creating patterns and offers you a practical method for solving problems. No other pattern cutting book considers the effects of individual fabrics and its approach is based on the appraisal of the fabric and body shape. [This book] is the revised and simplified edition of 'Fabric, Form and Flat Pattern Cutting'. It is fully illustrated and makes use of numerous practical examples. It also takes into account important new developments in fabrics - new fibres, new methods of fabric construction and new fabric finishes." -- Cover.
1. Fabric characteristics and garment shapes -- 2. Fabric testing -- 3. Selecting fabrics -- 4. Simple 'flat' cutting -- 5. Simple 'form' cutting -- 6. Cutting to fit the body form (woven fabrics) -- 7. Crossway cutting -- 8. Stretch fabrics and the body form -- 9. Complex 'flat' cutting -- 10. Supporting fabrics -- 11. Combining fabrics -- 12. Basic textile technology -- 13. Model stands and figures to reproduce -- 14. Creating the one-fifth and full-scale blocks (methods - manual, CAD or Internet access)
"Fabric, Form and Flat Pattern Cutting--an updated and simplified 3rd edition."
Includes index.
Keywords: Dressmaking -- Pattern design; Textile fabrics; Garment cutting